Answers provided at this link do not satify my question.
In Kenneth Rosan, the answer to this following sentence
“You cannot ride the roller coaster if you are under 4 feet tall unless you are older than 16 years old.”
is given as,
$(r \wedge \neg s) \rightarrow \neg q$
q: “You can ride the roller coaster.”
r: “You are under 4 feet tall.”
s: “ You are older than 16 years old.”
So, I broke down this compound sentence as follows:
“[You cannot ride the roller coaster] if [you are under 4 feet tall] unless [you are older than 16 years old.]”
Now, substituting variables in given compound sentence.
($\neg q$) if (r unless s).
Applying equivalence formula for Q if P $\Leftrightarrow$ P $\to$ Q
(r unless s) $\to$ ($\neg q$)
Now, solving for unless. So, (r unless s) $\Leftrightarrow$ ($\neg s \to r$) ref.
($\neg s \to r$) $\to$ ($\neg q$)
Again solving for $\to$ (implication), we get:
(s $\lor$ r) $\to$ ($\neg q$)
So, my derivation is obviously wrong and does not match with Kennet Rosen.
My Question: What mistake I did? and How to derive the given answer systematically?